How does a good environment affect firms’ productivity? evidence from urban public green spaces in China - Yang, Yalin; Ji, Xing; Deng, Liqian; Ma, Rufei (Frontiers in Energy Research, 2023)
The environment is one of the most fundamental factors that affects human economic activities. This article investigates whether good environment affects firms’ productivity. Using the urban public green spaces as the proxy of good environment, we find that firms located in cities with more public green spaces have relatively higher productivity, and the result remains robustness after considering the endogeneity problem. We also find that the productivity of those firms with more high-skilled employees are more likely to be affected by urban public green spaces, and they also have more innovation output which is believed as one of the important factors that affect firms’ productivity.